2018
DOI: 10.1055/a-0592-7039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluierung der mundgesundheitsbezogenen Lebensqualität bei seltenen Erkrankungen mit oraler Beteiligung

Abstract: The long distances travelled show the effort involved for patients, especially for those who come for a series of sessions. This has led to a call for a nationwide system of special consultation sessions for rare diseases with oral involvement - something NAMSE has also called for. There seems to be a markedly worse OHRQoL among all our patients. Overall, rare diseases with oral involvement appear to benefit more from an earlier diagnosis of the disease than do rare diseases without any oral involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Rare diseases have a negative impact on general health-related quality of life for patients [21]. Several studies suggest that rare diseases can also have an undesirable impact on the oral health-related quality of life due to associated abnormal dental and craniofacial findings [811, 2224]. Our study demonstrates for the first time that patients with LDS have worse OHRQoL when compared to both unaffected family members and the general U.S. population [4].…”
Section: Discussionmentioning
confidence: 99%
“…Rare diseases have a negative impact on general health-related quality of life for patients [21]. Several studies suggest that rare diseases can also have an undesirable impact on the oral health-related quality of life due to associated abnormal dental and craniofacial findings [811, 2224]. Our study demonstrates for the first time that patients with LDS have worse OHRQoL when compared to both unaffected family members and the general U.S. population [4].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group showed previously that the oral health-related quality of life (OHRQoL) is affected by rare diseases presenting oral manifestations [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have assessed this outcome from the perspective of people with rare diseases [9], the existing literature suggests this population presents a reduced oral health-related quality of life [9,10,11,12]. In this respect, oral manifestations of rare diseases may be negatively associated with their oral health perception [12].…”
Section: Introductionmentioning
confidence: 99%